2000
DOI: 10.1046/j.1365-2680.2000.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

The autonomic and sensory innervation of the smooth muscle of the prostate gland: a review of pharmacological and histological studies

Abstract: 1. We review literature demonstrating (a) the presence and (b) the actions of substances that mediate or modify neuroeffector transmission to the smooth muscle of the prostrate stroma of a number of species including man. 2. In all species studied prostatic stroma, but not secretory acini, receives rich noradrenergic innervation. Stimulation of these nerves causes contractions of prostate smooth muscle that are inhibited by guanethidine and by alpha1-adrenoceptor antagonists that probably act at the alpha1L-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 132 publications
0
80
0
8
Order By: Relevance
“…Physical denervation of the prostate by sectioning the hypogastric nerve in a rat model induces prostatic atrophy [70]. Similarly, Doggweiler et al [71], using chemical denervation by injecting BoNT into the rat prostate, reported a generalized atrophy and apoptosis of glandular elements.…”
Section: Prostate Bont Applicationmentioning
confidence: 98%
“…Physical denervation of the prostate by sectioning the hypogastric nerve in a rat model induces prostatic atrophy [70]. Similarly, Doggweiler et al [71], using chemical denervation by injecting BoNT into the rat prostate, reported a generalized atrophy and apoptosis of glandular elements.…”
Section: Prostate Bont Applicationmentioning
confidence: 98%
“…30 However, tachykinins can act at tachykinin NK 2 receptors to facilitate contractions in the human prostate 31 and have similar enhancing effects on nerve-mediated contractions in the guinea-pig, but not the rat, prostate. 30 Similarly, calcitonin gene-related peptide (CGRP)-immunoreactive nerves are sparsely distributed throughout the human, guinea-pig and rat 14,32,35,36 prostates. However, CGRP relaxes prostates taken from rats, but not guinea-pigs.…”
Section: Animal Prostate Models Of Human Prostate Contractilitymentioning
confidence: 99%
“…However, CGRP relaxes prostates taken from rats, but not guinea-pigs. 32,35,36 The physiological role of CGRP in human prostate contractility has not yet been investigated.…”
Section: Animal Prostate Models Of Human Prostate Contractilitymentioning
confidence: 99%
“…The prostatic function is under the infl uence of autonomic innervation and acetylcholine stimulates the gland secretion and growth, and noradrenaline induces prostatic contraction (PENNEFATHER, 2000). Botulinum toxin type A (BT-A) inhibits the release of acetylcholine into the synaptic junction decreasing the muscle tone in skeletal and smooth muscles (CHANCELLOR et al, 2008).…”
Section: Introductionmentioning
confidence: 99%